ENGLISH MAJOR GRADUATES’ CAREERS AND ARTIFICIAL INTELLIGENCE: WORKPLACE EXPERIENCES AND IMPLICATIONS FOR EMPLOYABILITY PREPARATION - Sararit, Jirawoot; Tiyarattanachai, Pitchaya; Keadplang, Kittiya; Sathongeay, Sunitra; Phurinan, Tanaporn (วารสารปัญญาภิวัฒน์, 2026)
This study investigates English major graduates’ career sectors, their use of Artificial Intelligence (AI) in workplace tasks, and the human skills they perceive as non-substitutable by AI. Using a mixed-methods design, data were collected through an online questionnaire from 109 graduates of a Communicative English for Business program in Thailand and supplemented by semi-structured interviews with 15 graduates from diverse employment sectors. Descriptive statistics were used to analyze survey data, while interview transcripts were summarized thematically to deepen interpretation. The findings show that most graduates were employed in service-oriented, modern trade, and health-related industries where communication and customer interaction were central. AI was widely used to support tasks including documentation, customer service, marketing, recruitment, education, administrative operations, and health-service coordination. However, graduates consistently identified core human capabilities—particularly emotion and empathy, complex problem-solving, interpersonal communication, creativity, and professional responsibility—as functions that AI could not replace. These results indicate that AI operates primarily as a supportive tool that enhances efficiency rather than replacing human roles in English-major careers. The study highlights the importance of integrating AI-blended learning approaches that combine language development with authentic and AI-supported workplace tasks while intentionally cultivating human-centered competencies to prepare graduates for sustainable employability in AI-augmented professional environments.